2013
DOI: 10.1159/000345770
|View full text |Cite
|
Sign up to set email alerts
|

Tear Film Osmolarity in Patients with Diabetes Mellitus

Abstract: Purpose: To compare tear film osmolarity (TFO) between patients with diabetes mellitus (DM) and normal healthy individuals. Methods: In this prospective case-controlled study, the TFO in 46 normal subjects (control group) and 55 patients with DM (study group) was evaluated. TFO in milliosmole (mOsm) was measured by using an auto-osmometer. The serum levels of glycosylated hemoglobin (HbA1c) and blood glucose in all participants were also measured. Mean outcome measures were TFO and its relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 42 publications
2
27
1
Order By: Relevance
“…One possible explanation for the difference in tear osmolarity is that Sağdik et al required an eye drop washout period of 12 hours and ointment washout of 5 days, whereas our study required that subjects not use any eye drops for a period of 2 hours as recommended by TearLab and as employed by other tear osmolarity studies 25,26,30. Because 30% of our subjects reported using artificial tears, future studies in our population with a longer washout period may find a maximum tear osmolarity closer to the value found by Sağdik et al22…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…One possible explanation for the difference in tear osmolarity is that Sağdik et al required an eye drop washout period of 12 hours and ointment washout of 5 days, whereas our study required that subjects not use any eye drops for a period of 2 hours as recommended by TearLab and as employed by other tear osmolarity studies 25,26,30. Because 30% of our subjects reported using artificial tears, future studies in our population with a longer washout period may find a maximum tear osmolarity closer to the value found by Sağdik et al22…”
Section: Discussionsupporting
confidence: 85%
“…However, tear osmolarity in our diabetic population was lower than that found by Sağdik et al,22 who found an average tear osmolarity of 320±22 mOsm/L in diabetic subjects and 308±18 mOsm/L in controls. Glycemic control was similar in our study and that of Sağdik et al, with a mean HbA1c of 7.9% in both studies.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…The observed mean values of tear osmolarity, BUT and Schirmer I test were 314.2±11.4 mOsm/L, 6.9±3.9 sec and 9.4±4.2 mm, respectively (7). Higher tear osmolarity (mean value 320.40±21.80 mOsm/l) has been also noted in diabetic subjects, where it was related to the duration of Diabetes Mellitus (19). The raised proptosis and lid fissure width appeared to be the reasons for tear hyperosmolarity (mean value 290.80±13.58 mOsm), as assessed by an auto-osmometer (OM-6030 AUTO STAT; Daiichi, Kyoto, Japan), in 21 subjects with thyroid ophthalmopathy (20).…”
Section: Discussionmentioning
confidence: 81%